Graciliblatta bella gen. et sp.n. - a rare carnivorous cockroach (Insecta, Blattida, Raphidiomimidae) from the Middle Jurassic sediments of Daohugou in Inner Mongolia, China - Liang, Jun-Hui; Huang, Wei-Long; Ren, Dong (Zootaxa, 2012)
Graciliblatta bella Liang, Huang et Ren, gen. et sp. n. is described from the Middle Jurassic Jiulongshan Formation of Daohugou in Eastern Inner Mongolia, China. Vein Sc of the new taxon has up to eight distinct branches, a remarkable diagnostic feature that distinguishes it from the other five known genera of the Raphidiomimidiae. The species was either extraordinary rare or lived remotely from the source area. It significantly expands the knowledge on diversity of carnivorous cockraoches - the least known cockroaches.